Assessment of executive functions using a 3D-video game in children and adolescents with ADHD - Takahashi, Nagahide; Ono, Tomihiro; Omori, Yuka; Iizumi, Misuzu; Kato, Hidekazu; Kasuno, Shinichi; Persing, Barry; Tsuchiya, Kenji J. (Frontiers in Psychiatry, 2024)
Objective Executive functions are important factors that affect the well-being of children with ADHD. Therefore, inclusion of a convenient assessment of executive dysfunction in diagnosis and treatment of ADHD patients is warranted. However, executive dysfunction assessment presently relies on lab-based neuropsychological tests and symptom rating scales. The present study examined the potential of a 3-D action puzzle video game to reflect ecologically valid executive functioning in pediatric ADHD patients. Methods Participant gameplay metrics were compared to both their Cambridge Neuropsychological Test Automated Battery (CANTAB) and Conners 3 Parent Form’s executive functioning subscale scores. Participants consisted of 33 ADHD and non-ADHD patients aged 8-21. Results Metrics from gameplay were associated with distinct CANTAB test scores, and a composite score from gameplay was significantly correlated with executive dysfunction from Conners 3. Conclusion For children with ADHD, cognitive domains related to executive function and overall real-life executive functioning appear to both be measurable via video games. It may be possible to develop individualized behavioral therapy based on the quantitative data obtained from the video game used in this study.